Ambiente familiar y su influencia en la seguridad emocional y afectiva de los niños-as del sector las Palmas, parroquia Pimocha, cantón Babahoyo - Palma Ramírez, Liceth María (2021)
Family environment constitutes the space in which a group of relatives lives who cooperate in economic life in the upbringing and teaching of children. Despite the importance of the family environment in learning values at home, it has been observed that, in some families, children live in a negative environment that focuses on the family environment, children with attitudes and behaviors that affect the interaction of parents and children, reaction and behavior that help to detect people with a lack of human quality to function properly in society. Through the collection of information made to parents and children, it was possible to identify the ineffectiveness of family education in some homes, which influences the emotional and affective state of children. Parents were and still are the first educators of their children; from them they receive the first teachings, as Fernando Azevedo says "education requires patience, indulgence, self-denial and sacrifice and it is more natural to find these qualities in parents." The family nucleus generates favorable conditions in the education of the children, and if this is not fulfilled and they are left in the care of anyone, it becomes a danger to society. The protection, love and care of other people is not enough for emotional and affective cultivation, which will cause problems at home